Incidence of Post-Op Sore Throat in Tertiary Care Hospital of Khyber Pukhtankhwa - Salma Jan, Syed Uzair, Jawad Mabood, Alishba Shahi, Gulalai Burki, Muhammad Ghazan Bashir, Sohaib Amin, Hizbullah Khan (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: To find out the incidence and frequency of post-Op sore throat in a tertiary care hospital. Study Design: Observational (cross sectional) Study. Setting: Department of Anesthesia Hayatabad Medical Complex Peshawar Khyber Pakhtunkhwa Pakistan. Duration of Study: This study was conducted from 1st November 2022 to 30th April 2023. Subjects and Methods: A total of 100 patients of both genders who underwent various types of surgical procedures under general anesthesia were admitted and followed in the post-operative period. After informed consent, patient selection was done through non probability consecutive sampling keeping inclusion and exclusion criteria in perspective and proformas were filled. Data was analyzed using Statistical software SPSS version 23.0 and results shown in the form of descriptive tables. Results: The total number of patients enrolled in the study were 104 out of which 44 were male and 60 were female with mean age of 41.1 ± 10.7. There was no significant association observed between sore throat and gender (p-value 0.630), age (p-value 0.367) size of ETT used (p-value 0.862) and duration of anesthesia (p-value 0.265). Conclusion: Post-operative sore throat is a regular occurring complication in patients however its incidence can be reduced by identifying the proper risk factors. Keywords: Anesthesia, intubation, Sore throat.